Co-occurring internalizing and externalizing psychopathology in childhood and adolescence: a network approach. - McElroy, Eoin; Shevlin, Mark; Murphy, Jamie; McBride, Orla (European Child & Adolescent Psychiatry, 2018)
The network approach suggests that psychopathology arises from complex associations between symptoms and may offer insight into the mechanisms that underpin psychiatric comorbidities. The transition from childhood to adolescence is a key period in the development of psychopathology, yet has rarely been considered from a network perspective. As such, the present study examined the network structure of internalizing and externalizing psychopathology from middle childhood through adolescence using data from the Avon Longitudinal Study of Parents and Children (ALSPAC; n = 4405). Eight DSM-IV disorders were assessed using maternal reports when children were aged 7.5, 10.5 and 14 years. Weighted, undirected networks were estimated and the relative importance of each node was assessed using three common measures of node centrality; strength, betweenness, and closeness. A consistent network structure emerged at all three time points; nodes clustered together in two regions of space broadly reflecting the internalizing and externalizing spectra. Permutation tests supported structural invariance across this developmental period. These spectra were bridged by numerous disorder-level interactions, the most consistent of which was between depression and oppositional defiant disorder (ODD). Furthermore, inspection of the centrality indices indicated that generalised anxiety disorder and ODD were the most central disorders in the networks. These findings demonstrate that symptom/disorder-level interplay and reciprocal influence are plausible mechanisms for the association between internalizing and externalizing psychopathology in childhood/adolescence.